Genetic and environmental determinants for disease risk in subsets of rheumatoid arthritis defined by the anticitrullinated protein/peptide antibody fine specificity profile. Issue 5 (1st June 2012) - Lundberg, Karin; Bengtsson, Camilla; Kharlamova, Nastya; Reed, Evan; Jiang, Xia; Kallberg, Henrik; Pollak-Dorocic, Iskra; Israelsson, Lena; Kessel, Christoph; Padyukov, Leonid; Holmdahl, Rikard; Alfredsson, Lars; et al.
Abstract : Objectives: To increase understanding of the aetiology and pathogenesis of rheumatoid arthritis (RA), genetic and environmental risk factors for RA subsets, defined by the presence or absence of different anticitrullinated protein/peptide antibodies (ACPAs) targeting citrullinated peptides from α-enolase, vimentin, fibrinogen and collagen type II, were investigated. Methods: 1985 patients with RA and 2252 matched controls from the EIRA case-control cohort were used in the study. Serum samples were assayed by ELISA for the presence of anticyclic citrullinated peptides (anti-CCP) antibodies and four different ACPA fine specificities. Cross-reactivity between ACPAs was examined by peptide absorption experiments. Genotyping was performed for HLA-DRB1 shared epitope (SE) alleles and the PTPN22 gene, while information regarding smoking was obtained by questionnaire. The association of genetic and environmental risk factors with different subsets of RA was calculated by logistic regression analysis. Results: Limited cross-reactivity was observed between different ACPA fine specificities. In total, 17 RA subsets could be identified based on their different ACPA fine specificity profiles. Large differences in association with genetic and environmental determinants were observed between subsets. The strongest association of HLA-DRB1 SE, PTPN22 and smoking was identified for the RA subset which was defined by the presence of antibodies to citrullinated α-enolase and vimentin. Conclusion: This study provides the most comprehensive picture to date of how HLA-DRB1 SE, PTPN22 and smoking are associated with the presence of specific ACPA reactivities rather than anti-CCP levels. The new data will form a basis for molecular studies aimed at understanding disease development in serologically distinct subsets of RA.